The Role of Agriculture in the Economic Development of Idofin-Igbanna, Kwara State Nigeria - Oyewale Peter Oluwaseun (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2022)
The study focus on the role of agriculture in the economic development of Idofin-Igbanna, agriculture remains one the major economic activities of Idofin, agriculture as an engine of growth and poverty reduction, because it assured food security. This paper however, focuses on the development of agriculture, the gender role in agricultural activities, it also attempts the role and impact of government in the prospect agricultural economy of Idofin-Igbanna. The paper obtained it's data from both primary and secondary sources which are made up of oral interview, books, journal articles, newspaper reports and government publications relevant to the topic.